A comprehensive decision assessment for trust evaluation in wireless sensor networks - Chakkarapani Sumathi Thilagasree; Thippan Jayakumar; Joseph Raj Vikilal Joice Brainy; Subramaniam Pragathi; Kang Daekook (Yugoslav Journal of Operations Research)
This study endeavors to tackle the pressing issue of network security within Wireless Sensor Networks (WSNs) through the introduction of an innovative integrated Pythagorean fuzzy-based method for evaluating network nodes. The primary aim is to enrich decision making frameworks within WSNs by furnishing a robust methodology for identifying and eradicating malevolent nodes. Investigation employs an integrated Pythagorean fuzzy-based methodology to appraise network nodes by scrutinizing specific trust attributes. Comparative assessment with alternative contemporary Multiple Criteria Decision Making (MCDM) trust models is conducted to gauge the effectiveness of the proposed strategy. The results underscore the efficacy of the integrated Pythagorean fuzzy-based approach in bolstering network security through the precise identification and elimination of malicious nodes. Comparative analysis with other MCDM trust models highlights the superiority of the proposed approach in evaluating network nodes based on trust attributes. In light of the findings, it is advised to integrate fuzzy decision analysis methodologies into decision making systems for WSNs to enhance network security. Additionally, future research endeavors could concentrate on refining and expanding upon the proposed methodology to effectively address emerging security challenges within WSNs.